THE COMPARISON OF UNESCAP'S CHARACTERISTICS OF GOOD GOVERNANCE AND ISLAMIC CHARACTERISTICS OF GOVERNANCE FOR PUBLIC SERVICES REFORM IN INDONESIA - Wisber Wiryanto (Faculty of Economics and Business, Hasanuddin University, 2018)
Good governance is a global and sustainable issue. International institutions offer the concept of good governance for bureaucracy and public services reform to various countries. Indonesia is one of the countries that have implemented and developed the concept of good governance.However, the establishment of such structures and regulations, is not a guarantee for improving the effectiveness of good governance implementation. In connection with the above mentioned issues, it is deemed necessary to conduct researc. The reasons of consideration that the majority of Indonesia's population adheres to Islam as great potential toward Islamic governance. This study is conducted to answer the problem formulation, what is similarities and differences between UNESCAP's Characteristics of Good Governance and Islamic Characteristics of Governance? The study used library research method, based on Holy Qur'an and Hadith Nabawi, relevant textbooks and websites, with direct observation in the field. Collecting and analyzing data based on descriptive qualitative method. This study was conducted in Indonesia, in the first half of 2018. Concluded, Islamic characteristics of governance consist of: shari’ah, ‘adl, ta’awun, bayan, itqan & tawazun, shura, at-tabayun and mas’uliyah. There are similarities of categories, and differences the annotation of categories between UNESCAP's characteristics of governance and Islamic Characteristics of Governance. As an implication then government officials must apply Islamic governance and ethics for public service reform in Indonesia.